Ethnography, Fidelity, and the Evidence that Anthropology Adds: Supplementing the Fidelity Process in a Clinical Trial of Supported Employment. (21st April 2014) - Smith‐Morris, Carolyn; Lopez, Gilberto; Ottomanelli, Lisa; Goetz, Lance; Dixon‐Lawson, Kimberly
<x xml:space="preserve">Abstract</x> This discussion considers the role and findings of ethnographic research within a clinical trial of supported employment for veterans with spinal cord injury. Contributing to qualitative evaluation research and to debates over anthropological evidence vis‐à‐vis clinical trials, we demonstrate how enactors of a randomized controlled trial can simultaneously attend to both the trial's evidentiary and procedural requirements and to the lived experiences and needs of patients and clinicians. Three major findings are described: (1) contextual information essential to fidelity efforts within the trial; (2) the role of human interrelationships and idiosyncratic networks in the trial's success; and (3) a mapping of the power and authority structures relevant to the staff's ability to perform the protocol. We emphasize strengths of anthropological ethnography in clinical trials that include the provision of complementary, qualitative data, the capture of otherwise unmeasured parts of the trial, and the realization of important information for the translation of the clinical findings into new settings.